Practical and General Amplify-and-Forward Designs for Cooperative Networks - Qijia Liu; Wei Zhang; Xiaoli Ma (2010 Proceedings IEEE INFOCOM, 2010)
Cooperative networks allow the nodes relaying each other's messages to enhance the transmission reliability over wireless fading channels by achieving cooperative diversity. Among the various relaying protocols, the amplify-and-forward (AF) strategy is well studied for its simplicity. However, to collect the cooperative diversity, there are two main issues that the AF protocol is facing. One is that the channel state information (CSI) of the source-to-relay link (i.e., two-hop CSI) is needed at the destination. The other concern is that the power scaling factor (PSF) and output signals at the relay are unbounded. These two issues make AF less practical in resource constrained networks, e.g., blind and peak power constrained relays. In this paper, we reveal the necessary and sufficient conditions on designing the PSF for the maximum ratio combining (MRC) receiver at the destination with two-hop (TH) CSI to achieve full cooperative diversity. Furthermore, we also provide the necessary conditions on the PSF design so that MRC with only one-hop (OH) CSI still collects full cooperative diversity. These designs make AF strategies more general and practical. The theoretical analysis is corroborated by numerical simulations.